The transforming landscape of cannabis in southwest Michigan: a case study of regulations and the role of small-scale growers. (4th July 2022) - Reid, Matt
Abstract: This article examines the nature of and controversies within southwest Michigan's unique cannabis community during the state's imposition of a new regulatory model for medical cannabis businesses. These transformations occurred at the same time voters in the state struck down prohibition in 2018, arguably facilitating an even more anomic environment for medical cannabis patients and stakeholders. Data presented here comes from an eclectic mix of key informant interviews ( n = 9), focus groups of cannabis patients ( n = 21), informal researcher observations, and news reports. These are combined to create a case study that illuminates a variety of tensions during a transformational time. Results are then broken down between two overarching themes—How new regulations favoring big businesses made medical cannabis scarce for patients, and how the inclusion of caregivers in the new regulatory system may have prevented such a scarcity. Following the results is a discussion which synthesizes the literature on medical cannabis social movements and the cannabis subculture with the tensions and controversies documented in Michigan. The article concludes with implications and practical strategies for regulatory bodies as both medical and adult-use cannabis moves from the underground and into the formal economy.